2017
DOI: 10.1038/s41598-017-06813-9
|View full text |Cite
|
Sign up to set email alerts
|

Dietary acrylamide exposure was associated with mild cognition decline among non-smoking Chinese elderly men

Abstract: The aim of the study is to explore the longitudinal association of dietary acrylamide exposure with cognitive performance in Chinese elderly. The analysis was conducted among 2534 non-smoking elderly men and women based on a prospective study, Mr. and Ms. OS Hong Kong. Dietary acrylamide intake was assessed by food frequency questionnaires with data on local food contamination, derived from the first Hong Kong Total Diet Study. Global cognitive function was assessed by Cantonese version of Mini-Mental State Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 33 publications
0
18
1
Order By: Relevance
“…[ 241–246 ] Cooking and processing of food at a high temperature can produce toxic compounds, such as advanced glycation end products (AGEs), heterocyclic aromatic amines (HAAs), acrylamide, and acrolein. [ 247–251 ] The potential role of dietary toxins is being studied for AD relevance as they are encountered in higher doses and more frequently through one's life span compared to other environmental contaminants. [ 239,252 ]…”
Section: Environmental Neurotoxicants That Alter Bace1mentioning
confidence: 99%
See 1 more Smart Citation
“…[ 241–246 ] Cooking and processing of food at a high temperature can produce toxic compounds, such as advanced glycation end products (AGEs), heterocyclic aromatic amines (HAAs), acrylamide, and acrolein. [ 247–251 ] The potential role of dietary toxins is being studied for AD relevance as they are encountered in higher doses and more frequently through one's life span compared to other environmental contaminants. [ 239,252 ]…”
Section: Environmental Neurotoxicants That Alter Bace1mentioning
confidence: 99%
“…[241][242][243][244][245][246] Cooking and processing of food at a high temperature can produce toxic compounds, such as advanced glycation end products (AGEs), heterocyclic aromatic amines (HAAs), acrylamide, and acrolein. [247][248][249][250][251] The potential role of dietary toxins is being studied for AD relevance as they are encountered in higher doses and more frequently through one's life span compared to other environmental contaminants. [239,252] Advanced glycation end products: AGEs are naturally present in uncooked animal-derived foods; high-temperature cooking accelerates the formation of new AGEs within these foods.…”
Section: Dietary Toxinsmentioning
confidence: 99%
“…In addition, fried vegetables were also associated with a slower SRT. This could be due to acrylamide produced in carbohydrate-rich food during frying, another high-temperature cooking process (18,19) . However, fried potatoes, a carbohydraterich food, did not show a similar negative association with reaction times.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to carbohydrate-rich food heated to high temperatures, acrylamide can be produced, a known neurotoxin and carcinogen (18) . Currently, evidence regarding effects of acrylamide on cognitive function is limited, but a study among non-smoking elderly Chinese men found that dietary acrylamide exposure was associated with mild cognitive decline (19) . Both loss of nutrients and production of hazardous compounds can vary by cooking method, and at present, very little information exists regarding the possible influence of cooking methods on cognitive function.…”
mentioning
confidence: 99%
“…Biasibetti et al [ 181 ] demonstrated that long-term supplementation of EGCG with a dose of 10 mg/kg BW/day for four weeks, to the ICV-STZ induced rats, increased GPX activity by 105% as compared to control, and decreased NO and ROS levels generated in the hippocampus by 100% and 105% compared to control, respectively. Chronic exposure to the industrial chemical, such as acrylamide, could also result in neurotoxicity, whereby accumulation of acrylamide from dietary sources has been linked to mild cognition decline in elderly Chinese non-smoking men [ 182 ]. Again, treatment with ECGC at 20mg/kg BW/day for 14 days in rats attenuated the neurotoxic effect of acrylamide by significantly increasing the GSH level to 35 compared to 22 nmol/g tissue in untreated acrylamide-induced neurotoxicity rats in the cerebral cortex, which was comparable to the effects of vitamin E [ 183 ].…”
Section: Dysregulation Of Antioxidant and Pro-oxidant Enzymesmentioning
confidence: 99%